FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN TINGKAT KERACUNAN PESTISIDA PADA TENAGA PENJUAL PESTISIDA - Mualim, Mualim (Politeknik Kesehatan Kemenkes Bengkulu, 2013)
The purpose of this study to determine the risk factors that have a relation to the rate of pesticide poisoning on the seller / entrepreneur / dealers (distributors). This study is a survey with a cross-sectional approach. Subjects were all salespeople pesticides in Bengkulu city by 52 people (total sampling). The dependent variable is the rate of pesticide poisoning, while the independent variable is the length of service, knowledge, attitudes, practices and use of protective equipment. Statistical analysis using Chi Square followed Logistic Regression with SPSS significance level (p <0.05). Based on the results of blood cholinesterase activity of 52 subjects, the majority were poisoned as many as 41 people (78.85%), and normal as many as 11 people (21.15%). Chi Square statistical test results show, there are several risk factors associated namely, knowledge (p = 0.000), attitude (p = 0.019), practice (p = 0.040), and the use of personal protective equipment (p = 0.001), whereas the test results Multifariate statistics using Logistic Regression, of bebarapa related factors turned out to be only 2 (two) were significantly associated, namely knowledge (p = 0.006 to OR = 25.896) and the use of personal protective equipment (p = 0.018 to OR = 9.873).